PENGARUH PENGGUNAAN MODEL SILENT DEMONSTRATION DENGAN MEDIA POSTER TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII SMPN 1 LABUHAN HAJI - S. Martina Nidia Rahmawati M. (Bioscientist : Jurnal Ilmiah Biologi, 2013)
Various efforts approach in learning continues to be done, therefore in the implementation of teaching and learning teachers can choose the appropriate approach and method. This study aims to determine the effect of cooperative learning model type Silent Demonstration by using the poster media to increase the biology learning outcomes in grade VII students SMPN 1 Labuhan Haji Year 2012/2013 Lesson. This type of research is a quasi experiment using Postest Only, Non-Equivalent Control Group Design. The population in this study were all students of class VII SMPN 1 Labuhan Haji and the sample used were the students of class VII A which amounted to 36 people as the experimental class and the students of class VII D which amounted to 36 people as the control class taken with Random Sampling technique. Technique of collecting data by using questionnaire to get data result of student's learning motivation and test to get data result of student learning. Result of t-test calculation for data of motivation at significant level 5% obtained t-table equal to 1,67 and t-count equal to 0,68 so tcount < ttabel meaning H0 accepted and result of t-test for learning result at significant level 5% obtained ttable of 1.67 and tcount of 22.5 so thitung > ttabel which means H0 rejected (Ha accepted). Thus the silent demonstration model can give a significant positive effect on the learning outcomes and on the motivation of students in grade VII SMPN 1 Labuhan Haji.